2019
DOI: 10.3389/fneur.2019.00471
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Tremor Dominant and Postural Instability Gait Difficulty Subtypes During the Progression of Parkinson's Disease: Analysis of the PPMI Cohort

Abstract: Background: Classifying PD into tremor dominant (TD) and postural instability gait difficulty (PIGD) subtypes may have several limitations, such as its diagnostic inconsistency and inability to reflect disease stage. In this study, we investigated the patterns of progression and dopaminergic denervation, by prospective evaluation at regular time intervals. Methods: 325 PD dopamine replacement drug-naïve patients (age 61.2 ± 9.7, M:F = 215:110) were enrolled. Patients were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…Compared with PD patients with optimal plasma exosomal BDNF, patients with low plasma exosomal BDNF levels in this study were likely to exhibit more significant dysfunction in PIGD-associated motor symptoms, which affect the quality of life and are often unmitigated by medical treatment [20]. Considering that PIGD is an unfavorable subtype of PD that may transform from benign subtypes of PD [21], plasma exosomal BDNF level may potentially predict and monitor disease progression in PD.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Compared with PD patients with optimal plasma exosomal BDNF, patients with low plasma exosomal BDNF levels in this study were likely to exhibit more significant dysfunction in PIGD-associated motor symptoms, which affect the quality of life and are often unmitigated by medical treatment [20]. Considering that PIGD is an unfavorable subtype of PD that may transform from benign subtypes of PD [21], plasma exosomal BDNF level may potentially predict and monitor disease progression in PD.…”
Section: Discussionmentioning
confidence: 90%
“…These patients require unique management and should not be treated the same way as other PD patients, especially deep brain stimulation [43]. Besides, patients with PD of non-PIGD subtypes may convert to the PIGD subtype as the disease progresses [21]; thus, a reliable blood biomarker is required to make early prediction possible.…”
Section: Discussionmentioning
confidence: 99%
“…Although reference 97 showed no significant differences in dopaminergic uptake between TD and AR, two later studies of theirs showed TD had increased dopaminergic uptake in the caudate and anterior putamen compared to AR patients 94, 98 and a separate study showed TD to have less severe striatal dopaminergic defects compared to AR 99 . Further comparisons between TD and PIGD show increased dopamine uptake in TD in the caudate, putamen, and IPL (Brodmann area [BA] 40), 100 and although one study showed no differences in FP‐CIT uptake in the striatum between the TD and nTD 95 another reported TD to have enhanced GPi–MC and putamen–MC coupling compared to nTD in the MAH 34 …”
Section: Molecular Imagingmentioning
confidence: 99%
“…aspects such as motor phenotype tend to be more ing to a common phenotype toward the end [14,15] of individuals with the TD phenotype will switch 344 to a PIGD phenotype over time [14,15,18]. An (alpha-synuclein [21], 5-hydroxyindoleacetic acid, glycine [12]) and degree of cardiac sympathetic denervation, for example [21].…”
Section: Subtyping By Designmentioning
confidence: 99%